Answer:
Below
Explanation:
5)
The sequence includes the terms 3,6,9,12,15.. and so on
Notice that each time we add 3.
The first term is 3.
We can see it in a different way
● 3 = 3×1
● 6 = 3×2
● 9 = 3×3
● 12 = 3×4
Let 1 be n. Notice what happens
● 3 = 3n
● 6 = 3 × (n+1)
● 9 = 3 × (n+2)
● 12 = 3 × (n+3)
So we can express it as.
● a1 = 3 × 1 =3
● a2 = 3×2 =6
● a3 = 3×3 = 9
So the third term is a3 wich is 9
● a6 = 3×6 = 18
So the sixth term is 18 .
■■■■■■■■■■■■■■■■■■■■■■■■■■
6)
the sequence is defined by:
● f(n-1) = -0.5 f(n)
Repalce n-1 with n and n with n+1
● f(n) = -0.5 f(n+1)
So to get a term you must multiply the next one by -0.5
The first term in the sequence is 120.
● 120 = -0.5 f(n+1)
● f(n+1) = 120/-0.5
● f(n+1) = -60
So the second term is -60